Cold Agglutinin Disease Presenting with Acute Encephalopathy in an Elderly Patient with Multiple Comorbidities: A Case Report and Laboratory Diagnostic Perspective - Desak Agung Indah Praharsini Dewi; I Gusti Ayu Wiradari Tedja; Made Ayu Vita Prianggandanni (Sriwijaya Journal of Internal Medicine, 2026)
Introduction: Cold agglutinin disease (CAD) is a rare form of autoimmune hemolytic anemia caused by monoclonal immunoglobulin M autoantibodies that bind to red blood cells at temperatures below 37 degrees Celsius. CAD typically manifests with chronic hemolytic anemia in elderly patients, but presentations with acute, severe complications remain infrequent. Case presentation: We report a 70-year-old male patient who presented with acute decreased consciousness lasting 2 hours, preceded by one week of cough and fever. Initial clinical evaluation suggested sepsis-associated encephalopathy. However, a comprehensive laboratory investigation, including peripheral blood smear and direct Coombs test, revealed CAD as the underlying diagnosis. Critical laboratory finding was marked mean corpuscular hemoglobin concentration elevation to 43 g/dL, exceeding physiologic maximum and indicating erythrocyte agglutination interference. Positive Coombs test with immunoglobulin G sensitization and positive cold agglutinin titer confirmed the diagnosis. The patient had significant comorbidities, including chronic kidney disease Stage V, type 2 diabetes mellitus, and heart failure with coronary artery disease. The patient subsequently underwent supportive care with cooling precautions, and clinical improvement was noted. Conclusion: This case exemplifies how careful attention to laboratory pattern recognition, particularly supraphysiologic mean corpuscular hemoglobin concentration values, can facilitate the diagnosis of CAD in elderly patients presenting with acute multisystem complications. The role of clinical pathology in the diagnostic identification of rare hematologic disorders deserves emphasis in medical education and clinical practice.